Functional biomaterials for tendon/ligament repair and regeneration. (5th September 2022) - Tang, Yunkai; Wang, Zhen; Xiang, Lei; Zhao, Zhenyu; Cui, Wenguo
Abstract: With an increase in life expectancy and the popularity of high-intensity exercise, the frequency of tendon and ligament injuries has also increased. Owing to the specificity of its tissue, the rapid restoration of injured tendons and ligaments is challenging for treatment. This review summarizes the latest progress in cells, biomaterials, active molecules and construction technology in treating tendon/ligament injuries. The characteristics of supports made of different materials and the development and application of different manufacturing methods are discussed. The development of natural polymers, synthetic polymers and composite materials has boosted the use of scaffolds. In addition, the development of electrospinning and hydrogel technology has diversified the production and treatment of materials. First, this article briefly introduces the structure, function and biological characteristics of tendons/ligaments. Then, it summarizes the advantages and disadvantages of different materials, such as natural polymer scaffolds, synthetic polymer scaffolds, composite scaffolds and extracellular matrix (ECM)-derived biological scaffolds, in the application of tendon/ligament regeneration. We then discuss the latest applications of electrospun fiber scaffolds and hydrogels in regeneration engineering. Finally, we discuss the current problems and future directions in the development of biomaterials for restoring damaged tendons and ligaments. Graphical Abstract: